2020
DOI: 10.1039/d0cp04825a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding benzyl alcohol aggregation by chiral modification: the pairing step

Abstract: A combination of linear infrared and Raman spectroscopy in supersonic slit jet expansions is used to clarify the conformational preferences in the dimer of the transiently chiral benzyl alcohol (phenylmethanol)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 76 publications
3
48
0
Order By: Relevance
“…16. The relative stability of the rotamers was examined in detail in previous publications, and it was demonstrated that only the gauche conformation is detected in a supersonic expansion, [13][14][15][16][17][18] just as in the gas phase at room temperature. 39 The four-fold degenerate minima are connected by reflection on the ring plane or through a plane perpendicular to the ring.…”
Section: Bnoh Monomermentioning
confidence: 97%
See 3 more Smart Citations
“…16. The relative stability of the rotamers was examined in detail in previous publications, and it was demonstrated that only the gauche conformation is detected in a supersonic expansion, [13][14][15][16][17][18] just as in the gas phase at room temperature. 39 The four-fold degenerate minima are connected by reflection on the ring plane or through a plane perpendicular to the ring.…”
Section: Bnoh Monomermentioning
confidence: 97%
“…A full-range two-dimensional relaxed scan of the conformational space is available in the ESI of Ref. 16. The relative stability of the rotamers was examined in detail in previous publications, and it was demonstrated that only the gauche conformation is detected in a supersonic expansion, [13][14][15][16][17][18] just as in the gas phase at room temperature.…”
Section: Bnoh Monomermentioning
confidence: 99%
See 2 more Smart Citations
“…With the recent insights brought by these experiments on increasingly larger chiral organic molecules, our understanding of chiral recognition has slowly departed from the more simplistic "three-point" interaction picture to pairing models where weak interactions play a decisive act. Moreover, the balance of dispersion and electrostatic interactions needs to be considered if one is to decode the nature of the contact points that mediate the molecular fit and hence chiral recognition [33][34][35][36] .…”
mentioning
confidence: 99%